Parents and Children Talk : The Family Dynamics of English Language Proficiency - Barry R. Chiswick; Yew Liang Lee; Paul W. Miller (Institute for the Study of Labor (IZA), 2004)
This paper extends the analysis of the acquisition of destination language proficiency among immigrants by explicitly incorporating dynamics among family members – mother, father and children. Single equation, bivariate, and four-state (multivariate) probit analyses are employed. Immigrant English language skills are greater the younger the age at migration, the longer the duration of residence, the higher the level of education, and for immigrants not from Asia. Large positive correlations in the unmeasured determinants of proficiency exist between spouses, between siblings, and between parents and children, although the latter relationship is stronger for the mother.
Keywords: J16; J15; J61; J24; 330; immigrants; language; family; multinominal probit; Migranten; Englisch; Familiensoziologie; Schätzung; Fremdsprache; Australien